2023
DOI: 10.3389/fpsyt.2023.1173755
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of East Asian dementia caregivers in filial culture: a systematic review and meta-analysis

Abstract: BackgroundWith the aging population in East Asia, the prevalence of dementia and the need for patient care is increasing. Family caregivers of people with dementia are at risk of physical and mental health problems. Filial piety culture regulates relationships within East Asian families and effects the well-being and behavior of dementia family caregivers (CGs).ObjectiveTo systematically assess the experience of East Asian dementia caregivers in filial culture. Methods: Electronic databases, including MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…However, it has been criticized for its unidimensional scale structure that allows extent of burden to be evaluated using the total scale score only (Tu et al, 2022) and its introduction 30 years ago for a Western cultural context. Wang et al (2023) reported that the strong sense of filial obligation rooted in Confucian culture influences the burden of care perceptions of caregivers of patients with dementia, with stronger levels of perceived filial obligation associated with greater resistance to asking for outside help or using formal services. Because DCBS was developed to identify the burden attributes of caregivers living in a Confucian cultural setting, it may be expected to be more useful in measuring this burden in countries/societies influenced by these cultural mores.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been criticized for its unidimensional scale structure that allows extent of burden to be evaluated using the total scale score only (Tu et al, 2022) and its introduction 30 years ago for a Western cultural context. Wang et al (2023) reported that the strong sense of filial obligation rooted in Confucian culture influences the burden of care perceptions of caregivers of patients with dementia, with stronger levels of perceived filial obligation associated with greater resistance to asking for outside help or using formal services. Because DCBS was developed to identify the burden attributes of caregivers living in a Confucian cultural setting, it may be expected to be more useful in measuring this burden in countries/societies influenced by these cultural mores.…”
Section: Discussionmentioning
confidence: 99%
“…For children, this perceived duty perhaps aligns with the concept of filial piety. 31,32 Our study did not explore the familial relationship (i.e., parental vs. sibling) to determine the extent to which this duty is felt. However, a study conducted in Norway shows that this sense of duty is perceived regardless of whether the relationship is strained or not.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Asian countries have many challenges for family caregivers due to their aging populations. 10 Therefore, family nursing is becoming increasingly important in public health.…”
Section: Discussionmentioning
confidence: 99%